2002
DOI: 10.1002/path.1106
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hypoxia‐inducible heme oxygenase‐1 in the myocardium after left ventricular mechanical support

Abstract: Left ventricular assist devices (LVAD) may improve cardiac function. The pathogenesis of this phenomenon, called 'reverse remodelling', is not completely elucidated. To examine the hypothesis that LVAD support eliminates tissue stress by reducing local hypoxia, the distribution of heme oxygenase-1 (HO-1), a stress protein inducible by hypoxia, was examined in vivo and in vitro. The immunoreactivity for HO-1 was semi-quantitatively analysed in left ventricular tissue of 23 patients (14 dilated cardiomyopathy (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 27 publications
0
12
0
1
Order By: Relevance
“…The cardio protective role of fumarate has also been shown in knockout mice lacking the fumarate hydratase enyme to be mediated via up regulation of nrf-2 and the subsequent antioxidant targets [26]. The HO-1 protein has been shown to be up regulated in failing hearts and the effect reversed when these patients were supported on left ventricular assist devices [27]. …”
Section: Role Of Antioxidant Targets Of Nrf-2 In Cardiomyopathymentioning
confidence: 99%
“…The cardio protective role of fumarate has also been shown in knockout mice lacking the fumarate hydratase enyme to be mediated via up regulation of nrf-2 and the subsequent antioxidant targets [26]. The HO-1 protein has been shown to be up regulated in failing hearts and the effect reversed when these patients were supported on left ventricular assist devices [27]. …”
Section: Role Of Antioxidant Targets Of Nrf-2 In Cardiomyopathymentioning
confidence: 99%
“…Prior studies have reported that HO-1 is upregulated in human failing hearts [84] and in animal models of right ventricular failure [85]. The HO-1 expression in the noninfarct myocardium was increased four weeks after coronary ligation, and cardiomyocyte-specific HO-1 transgenic mice showed improved postinfarction survival and attenuated cardiac hypertrophy, interstitial fibrosis, oxidative stress, and apoptosis [86, 87].…”
Section: Role Of the Nrf2 Pathway In Ischemia-induced Cardiac Remomentioning
confidence: 99%
“…Overexpression of Hsp27 in myocytes confers protection against simulated ischemia (10). Another small molecular weight stress protein, Hsp32, has been shown to play an important role in cardiovascular adaptation to acute hypoxic stress (11). We reasoned that Hsp32 might also play a role in adaptation of infant human and rabbit heart to the stress of chronic hypoxia.…”
mentioning
confidence: 99%